Engineering Muscle Networks in 3D Gelatin Methacryloyl Hydrogels: Influence of Mechanical Stiffness and Geometrical Confinement - Costantini, Marco; Testa, Stefano; Fornetti, Ersilia; Barbetta, Andrea; Trombetta, Marcella; Cannata, Stefano Maria; Gargioli, Cesare; Rainer, Alberto (Frontiers in Bioengineering and Biotechnology, 2017)
In this work, the influence of mechanical stiffness and geometrical confinement on the 3D culture of myoblast-laden gelatin methacryloyl (GelMA) photo-crosslinkable hydrogels was evaluated in terms of in vitro myogenesis. We formulated a set of cell-laden GelMA hydrogels with a compressive modulus in the range 1÷17 kPa, obtained by varying GelMA concentration and degree of cross-linking. C2C12 myoblasts were chosen as the cell model, to investigate the supportiveness of different GelMA hydrogels on myotube formation up to 2 weeks. Results showed that the hydrogels with a stiffness in the range 1÷3 kPa provided enhanced support to C2C12 differentiation in terms of myotube number, rate of formation and space distribution. Finally, we studied the influence of geometrical confinement on myotube orientation by confining cells within thin hydrogel slabs having different cross-sections: i) 2000×2000 m, ii) 1000×1000 m and iii) 500×500 m. The obtained results showed that by reducing the cross-section—i.e., by increasing the level of confinement—myotubes were more likely restrained and formed aligned myostructures that better mimicked the native morphology of skeletal muscle.